2006
DOI: 10.1111/j.1540-8175.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Left Ventricular Diastolic Dysfunction, Identification of Pseudonormal/Restrictive Mitral Inflow Pattern and Determination of Left Ventricular Filling Pressure by Tei Index Obtained from Tissue Doppler Echocardiography

Abstract: TDE-Tei index increased with worsening of LV diastolic function and can effectively identify the pseudonormal/restrictive mitral inflow pattern. It also correlated with the echocardiographic parameters of LV systolic and diastolic function and filling pressure. It suggests that TDE-Tei index is a simple and feasible marker in assessing global LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 28 publications
2
44
3
1
Order By: Relevance
“…By contrast, Ea, E/Ea and LAVI presented unidirectional changes with worsening LV diastolic function. 14,[19][20][21][22][23][24] This pseudonormal phenomenon as LV diastolic dysfunction increases in E/A but not in Ea, E/Ea and LAVI may explain the different results between E/A and Ea, E/Ea and LAVI in the present study. In addition, previous studies found that decreased Ea and increased E/Ea and LAVI were correlated with LV diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 64%
“…By contrast, Ea, E/Ea and LAVI presented unidirectional changes with worsening LV diastolic function. 14,[19][20][21][22][23][24] This pseudonormal phenomenon as LV diastolic dysfunction increases in E/A but not in Ea, E/Ea and LAVI may explain the different results between E/A and Ea, E/Ea and LAVI in the present study. In addition, previous studies found that decreased Ea and increased E/Ea and LAVI were correlated with LV diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 64%
“…[16] MPI can be combined with TDI, and this combination eliminates the disadvantages of conventional MPI by not being affected from loading conditions and heart rate fluctuations. [27] Thus, TDI-derived MPI serves more reliable global cardiac performance. [27,28] Additionally, E/Em ratio, an important noninvasive marker of LV filling pressure, has been used increasingly in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Thus, TDI-derived MPI serves more reliable global cardiac performance. [27,28] Additionally, E/Em ratio, an important noninvasive marker of LV filling pressure, has been used increasingly in recent years. [29] It was reported that ROS in CAPD patients without diabetes affected glucose metabolism positively and decreased insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial early (Em) and atrial (Am) peak velocities (cm/s) and Em/Am ratio, and Sm À Em duration (isovolumic relaxation time: IVRT) were measured, as the time interval occurring between the end of Sm and the onset of Em, were determined as diastolic measurements. On the tissue Doppler images, the time interval from the end to the onset of the mitral annular velocity pattern during diastole (a m ) and the duration of the S-wave (b m ) were measured and used to calculate the DTI-Tei index as (a m À b m )/b m [16]. All diastolic parameters were measured in three consecutive cardiac cycles and averaged.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%